As manifestações da violência escolar na visão de crianças entre pensamentos falas e desenhos - MARQUES, Alda Lucia Silva (2020)
In order to understand how this phenomenon occours we developed this research as a qualitative one, located in a public school of Belém, focusing a study about violence, seeking for various forms of it expressed into the scholar ambient, through children look, through methodological instruments of observations, reports and children's graphics where the same difficulties are encountered. The problem of school violence is a harm that challenges Brazilian educators in the formation of individuals, putting in check a conception of values. In addition it interposes the education process and raises some difficulties about the grouth of expression and liberty thoughts. A reading of the authors that discusses the theme, specially Candau (2001), Abramovay (2002), Charlot(2002), Abramovay and Rua (2003) and Sarmento (2009), helped to develop this topic and base our discussion on them. Besides, we encountered some difficulties faced by the school in dealing with this phenomenon, allowing us to propose some suggestions for its confrontation.